The Development of the 3D Pageflip Professional-based e-Module on Energy Concepts - Adawiyah, Robiatul; Putri, Tri Suci Yolanda; Wilujeng, Insih (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
This study aimed to develop quality of the 3D Pageflip Professional-based e-module on energy concepts which has good quality and suitable for use in learning for junior high school grade 7. This type of research is a development that refers to the 4D development model with stages of define, design, develop, and disseminate. The research subjects were grade 7 students in one of the junior high schools in Yogyakarta. Data collection techniques using a questionnaire. Data analysis uses qualitative and quantitative analysis. The results showed that the 3D Pageflip Professional-based e-module on energy concepts that was developed had very good quality seen from the average rating of the material experts which was 87,5%, media experts was 89,6%, the science teacher was 95,8%, participant responses small class students by 83,7%, and the response of large class students is 84,5%. It was concluded that the 3D Pageflip Professional-based e-module on energy has a very good quality so that it is feasible to be used in the science learning process of seventh grade junior high school students.